Literature Review: Relationship Between Aedes Albopictus Mosquito Larvae Density and Dengue Fever Incidence Rate in Indonesia - Putra, Angga Pratama (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
Dengue Hemorrhagic Fever (DHF) continues to pose a growing global health threat, with over 90% of Indonesia’s regions affected. This study reviews the association between Ae. albopictus larvae density and DHF incidence in Indonesia through a Systematic Literature Review using PRISMA guidelines, analyzing journals from the past 10 years. The findings reveal that high larval density, especially in outdoor and public areas such as terminals and restaurants, plays a significant role in dengue transmission. Some locations reported vector indices exceeding thresholds (e.g., House Index >50%, Breteau Index >100), indicating high transmission risk. While not all studies demonstrated statistically significant correlations, most highlighted environmental conditions, types of water containers, sanitation, and population density as major contributing factors. The study concludes that effective DHF control requires a multisectoral strategy involving species-specific vector mapping and community-based interventions, targeting both domestic and public spaces to reduce mosquito breeding and mitigate disease spread